KONSEP ISYRAQY DAN HAKEKAT TUHAN (STUDI ATAS PEMIKIRAN AL-SUHRAWARDI AL-MAQTUL) - Ahmad, Rusdin (Institut Agama Islam Negeri (IAIN) Palu, 2006)
Al-Suhrawardi al-Maqtul is an Islamic mystitician who is very popular for his mistical teaching on isyraqiyah. Isyraqiyah is a symbol of goodness since it is the place of sunrise. Â In his mystical thought, al-Suharawardi who combines mysticism and philosophy eventually comes to the concept of Nur al-Anwar. He asserts that Allah is Nur al-Anwar that is the origin of everything and the whole event.Kata Kunci: Konsep isyraqy, hakekat Tuhan, nur al-anwar, al-Suhrawardi